1997
DOI: 10.3109/10398569709082105
|View full text |Cite
|
Sign up to set email alerts
|

The New Zealand Mental Health Strategy: Is it Making Any Difference?

Abstract: In June 1994, Government announced i the National Mental Health Strategy entitled ‘Looking Forward’ [1] outlining the goals and strategic directions for the development of mental health services in New Zealand for the next ten years, and which would underpin the on-going development and delivery of mental health services in this country. This strategy not only gave Government's policy directions for mental health, but provided the framework for resourcing mental health service (Table 1). In simple terms the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Over the last three decades the provision of mental health services in New Zealand, as in most western countries, has changed. Care, even for those with serious mental illness, is now commonly provided in the community, and includes intensive treatment, rehabilitation, and support services (Kemp, 1994;Joseph and Kearns, 1996;and Wilson, 1997). Appropriately managed and funded, community services are widely viewed as effective and preferable to hospital-based services.…”
Section: Community Mental Health Servicesmentioning
confidence: 99%
“…Over the last three decades the provision of mental health services in New Zealand, as in most western countries, has changed. Care, even for those with serious mental illness, is now commonly provided in the community, and includes intensive treatment, rehabilitation, and support services (Kemp, 1994;Joseph and Kearns, 1996;and Wilson, 1997). Appropriately managed and funded, community services are widely viewed as effective and preferable to hospital-based services.…”
Section: Community Mental Health Servicesmentioning
confidence: 99%
“…In mental health services unbundling resulted in further separationl3 of the social (e.g. accommodation) and health aspects of mental health (Wilson, 1997). Social needs were conceived of as disability costs whereas health needs were treatment.…”
Section: The Reforms Of the 1990smentioning
confidence: 99%
“…In theory, with the rights reforms and the number of providers available, the mid-1990s should have been a period when consumers would have had considerable choice. However, the Director of Mental Health reported that this was not the case, that the consumers lacked knowledge about their choices and were more confused than they were prior to the major reforms and expansion of service options (Wilson, 1997').…”
Section: Mental Health Consumer Movementmentioning
confidence: 99%
See 1 more Smart Citation